Outcome of the Pregnancy in Women with Increased Body Mass Index (BMI) - Khan, Shehreen (Indus Journal of Bioscience Research, 2025)
Objective: to evaluate and record the outcome of the pregnancy in women with increased body mass index (BMI). Settings: Department of Obstetrics and Gynecology, Allied Hospital Faisalabad. Study Duration: September 2024 to February 2025. Methodology: Using non-probability consecutive sampling, we enrolled 390 pregnant women with BMI >27 before 12 weeks of gestation and followed for maternal (GDM, pre-eclampsia) and fetal outcomes (shoulder dystocia, macrosomia). Results: Of the 390 pregnant women with BMI >27, the mean age was 28.66 ± 7.02 years and most (75.6%) had parity 0–3. A majority (63.1%) had BMI >30. Gestational diabetes was observed in 57.2%, pre-eclampsia in 8.7%, shoulder dystocia in 4.9%, and fetal macrosomia in 7.7%. No significant associations were found between these outcomes and age or parity (p > 0.05). Conclusion: This study reinforces the association between increased maternal BMI and adverse pregnancy outcomes, both regionally and globally. Given that obesity is a modifiable risk factor, early identification and counseling during antenatal visits are essential.